1997
DOI: 10.1172/jci119502
|View full text |Cite
|
Sign up to set email alerts
|

Kallistatin is a potent new vasodilator.

Abstract: Kallistatin is a serine proteinase inhibitor which binds to tissue kallikrein and inhibits its activity. The aim of this study is to evaluate if kallistatin has a direct effect on the vasculature and on blood pressure homeostasis. We found that an intravenous bolus injection of human kallistatin caused a rapid, potent, and transient reduction of mean arterial blood pressure in anesthetized rats. Infusion of purified kallistatin (0.07-1.42 nmol/kg) into cannulated rat jugular vein produced a 20-85 mmHg reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 21 publications
2
64
0
Order By: Relevance
“…Our previous study showed specific kallistatin-binding sites in rat aortic membrane proteins by Scatchard plot analysis, indicating potential kallistatin receptor(s) in mediating the vascular function of kallistatin (3). Kallistatin exhibits pleiotropic effects in inhibiting apoptosis, inflammation, and fibrosis in cardiac, renal, and vascular cells (6,7,12).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous study showed specific kallistatin-binding sites in rat aortic membrane proteins by Scatchard plot analysis, indicating potential kallistatin receptor(s) in mediating the vascular function of kallistatin (3). Kallistatin exhibits pleiotropic effects in inhibiting apoptosis, inflammation, and fibrosis in cardiac, renal, and vascular cells (6,7,12).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies indicate that kallistatin exerts pleiotropic effects such as vasodilation and inhibition of angiogenesis, tumor growth, inflammation, and oxidative stress, independent of tissue kallikrein (3)(4)(5)(6)(7). We showed that an intravenous bolus injection of human kallistatin caused a rapid and transient reduction of mean arterial blood pressure in anesthetized rats and that kallistatin induced relaxation in isolated aorta rings (3).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…8 Kallistatin is a member of the serine proteinase inhibitor (serpin) superfamily and was shown to have pleiotropic effects, including hypotension, anti-angiogenesis and antiinflammation. [9][10][11] Kallistatin gene delivery reduced ischemic myocardial inflammation and cardiomyocyte apoptosis at 1 day after acute ischemia/reperfusion injury. 12 Recently, we observed that increased oxidative stress after MI was associated with reduced circulating kallistatin levels, suggesting that kallistatin might be involved in the progression of oxidative cardiac damage.…”
mentioning
confidence: 99%
“…Another explanation, as suggested by our previous study (19), is that the apparent up-regulated TK metabolic activity is a function of its preactivation and half-life (t 1/2 ). Cellular TK, stored as inactive prekallikrein, is usually activated to TK which has proteolytic functions both within the endothelial cell and in the extracellular environment, until it is sequestered by inhibitors such as kallikrein binding protein (KBP), Protein C and kallistatin, resulting in a t 1/2 of several hours (44)(45)(46). Our anti-TK IgG detected both the prekallikrein stored within unchallenged HUVECs as well as TK released from HUVECs following activation by cervical cancer cell metabolites.…”
Section: Discussionmentioning
confidence: 99%